Hungarian industry in a context of settlement network and pattern - Kiss, Éva (Hungarian Geographical Bulletin, 2011)
The economic sectors have always played an important part in shaping the actual settlement pattern and network. Agriculture used to dominate for centuries, whereas industry came to the fore during the past two hundred years and its immanent changes have formed the settlement network. The present paper is aimed to describe the post-1989 impact of the transformation of the industry and its branches upon the settlement patt ern and prospects are outlined for the forthcoming decades. It has become evident that in the post-industrial phase the impact of the sector upon the sett lement network is less spectacular and rather indirect. The industrial enterprises have kept on concentrating in urban sett lements of the 20–50 thousand and over 100 thousand population size categories. The distribution of various branches of industry according to sett lement pattern shows considerable differences. In the future a further diminishment of the weight of the industry within the economy is anticipated and it is going to shape the settlement network to an even lesser extent.